Criterion of vehicle instability in floodwaters: past, present and future - Shah, S.M.H. (2019)
The stability of vehicles exposed to floodwaters on the roads should not be taken for granted, especially in floodplain areas. When a vehicle in floodwaters becomes unstable, it tends to become buoyant and, eventually, is washed away, putting occupants in extreme danger. Therefore, the characteristics of vehicle instability in floodwaters should be critically understood to prepare safety guidelines. This paper attempts to summarize different vehicle stability studies, which focused on parked vehicles for a range of flood depths, through experimental and theoretical analysis (1967â1993). However, modern vehicle designs mean there are different values for the stability limits under partial or full submergence with different braking conditions, orientations and ground slopes (2010â2017). Since all the reported studies are about static vehicles, this paper attempts to address, for the very first time, vehicles in motion and endangered by floodwaters. As such, the governing effect of incipient velocity for a partially submerged, non-stationary vehicle will be presented, under the consideration of two new parameters, namely rolling friction and driving force. Â© 2019, Â© 2019 International Association for Hydro-Environment Engineering and Research.